Fun for the Secret Seven - Blyton, Enid; Ross, Tony (Hodder Children's Books London, 2006)
The Seven are very fond of Tolly and his horse, Brownie, so they're determined to help out when Brownie is sick. But they need to find Tolly and Brownie somewhere to hide out - somewhere that dangerous horse thieves will never find. But where?